Capital Structure and Company Size Impact on Financial Performance: A Literature Review - Darman, Darman; Andini Hilumalo, Anggi Nur (Westscience Press, 2023)
The aim of this research is to investigate how capital structure, company size and financial risk influence the company's financial performance. Library research methods such as Google Scholar, Mendeley, Semantic Scholar, were used to write this Literature Review article. The research results show that the company's capital structure has a negative influence on financial performance. Company size has a positive effect on financial performance.